Penggunaan Media Kartu Angka Bergambar dalam Pembelajaran Anak Usia Dini Materi Pengenalan Angka dan Pengaruhnya Terhadap Motivasi Belajar - Rokhima Rokhima; Siti Khotijah; Indah Sumartiningsih (Laplace : Jurnal Pendidikan Matematika, 2019)
The role of learning media is very large in achieving learning messages, namely teaching material. Learning media can provide reinforcement of the explanations delivered by the teacher. Picture numeric card media is a visual media that can be used in learning or function as a learning media. The use of pictorial number card media in the Early Childhood Education (PAUD) learning is very suitable because it is relevant to the style of learning that is learning while playing. One kind of kindergarten learning material is the introduction of numbers and simple counting operations that are part of elementary level mathematics learning. Submission of numerical recognition learning materials and simple counting operations can be done using specially designed numeric card media. The use of multiple number card media in learning in this study is to see the effect on children's learning motivation. This type of research is quantitative causality, which is to see the effect of using numeric card media on children's learning motivation. Because of the quantitative type, this study uses statistical calculations through the SPSS version 22.0 program which includes a prerequisite test for normality and homogeneity, hypothesis testing with partial tests or different tests (T test). The results of this study indicate the influence of multiple number card media on early childhood learning motivation in numerical recognition learning materials and simple count operations Al-Mahrus Integrated Kindergarten, Siti Khotijah 1 PAUD and TK Labschool IKIP PGRI Jember even semester 2018/2019 academic year.